The cyclical behaviour of European bank capital buffers - Terhi Jokipii; Alistair Milne (Bank of Finland, 2006)
Using an unbalanced panel of commercial, savings and co-operative banks for the years 1997 to 2004 we examine the cyclical behaviour of European bank capital buffers.After controlling for other potential determinants of bank capital, we find that capital buffers of the banks in the accession countries (RAM) have a significant positive relationship with the cycle, while for those in the EU15 and the EA and the combined EU25 the relationship is significantly negative.We additionally find fairly slow speeds of adjustment, with around two-thirds of the correction towards desired capital buffers taking place each year.We further distinguish by type and size of bank, and find that capital buffers of commercial and savings banks, and also of a sub-sample of large banks, exhibit negative co-movement.Co-operative banks and smaller banks on the other hand, tend to exhibit positive cyclical co-movement.
URN:NBN:fi:bof-20140807210
Keywords: G21; G28; 330; bank capital; bank regulation; business cycle fluctuations